Acclimation temperature influences the thermal sensitivity of injury accumulation in Folsomia candida at extreme low and high temperatures - Micha Wehrli; Stine Slotsbo; Jian Ge; Martin Holmstrup (Current Research in Insect Science)
The importance of thermal acclimation for the Thermal Death Time (TDT) landscape of the common soil living springtail, Folsomia candida (Collembola, Isotomidae), was investigated. To this aim, we acclimated adult springtails at 10 °C (cold-acclimation) and 20 °C (warm-acclimation), respectively. In static thermal tolerance assays, we found the relationship between survival and exposure time at a number of stressful high and low temperatures. Using logistic modelling, we found, at each exposure temperature, the time until 50% mortality had been reached (Lt50). The exponential functions of TDT curves were found by linear regression of log10 Lt50 values against exposure temperature. Results showed that cold acclimation significantly increased cold tolerance and increased the temperature dependence of cold injury accumulation rate (increased the slope by 4 orders of magnitude) in F. candida. Hence, cold acclimation changed the status of this species from chill-susceptible to moderately chill-tolerant. The cellular injury accumulation at sub-zero temperatures was not related to freezing of body water in this study. Congruently, we found a significant negative effect of cold acclimation on heat tolerance and that cold acclimation decreased the thermal sensitivity of the heat injury accumulation rate. Different slopes of the TDT curves between acclimation groups indicated that acclimation shifted the proportional importance of cellular injury mechanisms or the nature of injury mechanisms. Finally, we compare and combine the TDT curves at extreme high and low temperatures with previously published results on longevity at benign temperatures (from 0 to 30 °C) and describe the full thermal niche of F. candida.